SISTEM KONTROL DAN MONITORING ATAP DAN LAMPU UNTUK TANAMAN MELON SECARA HIDROPONIK DENGAN ARDUINOCLOUD MELALUI WIFI MENGGUNAKAN SMARTPHONE ANDROID - Gumilang, Fajar; Pratama, Ilham; Bimantoro, Ananta Rio (University of Muhammadiyah Tangerang, 2024)
Melon is a fruit commodity that is very popular with almost everyone so it is not surprising that the volume of circulation in the market is on a large scale, but weather factors are the main cause of crop failure, it takes weather with rainfall of 1500 to 2000 mm / year and humidity of 50 to 70 percent every day so that melon plants grow well and have good fruit. To solve this problem, an automatic environmental control tool is needed. The solution that can be done is to design a roof control tool, monitoring and controlling lights to make it easier to care for melon plants. This study designs, creates and implements a rooftop monitoring and control system and lights for melon plants. This tool uses a sensor that sends commands to Arduino automatically using IoT and is operated using Arduino Cloud. This research tool uses an Abrometer sensor to detect rainfall as a rooftop controller, a PZEM sensor as a detector of the power load needed to run this tool, and a UV lamp to help the growth of melon plants. The results of this study are in the form of a prototype that is automatically controlled using the Internet of Things (IoT) and can function well.